188k views
0 votes
Help with substitution

Help with substitution-example-1

2 Answers

5 votes

Answer:

The answer will be listed below.

Explanation:

Since there is an x= 2y+3, you can plug that equation into x in the equation 2x-3y=7. You must find y first.

2(2y+3)-3y=7

Now distribute 2 and you will get 4y+6-3y=7.

Combine 4y and -3y and have an equation of y+6=7.

Subtract 6 to both sides and you will have an answer of y=1

Now since you found y, now find x. To find x, substitue y=1 into any equation listed (you'll get the same answer anyways). Let's use x=2y+3 as an example. Substitute the 1 for y.

x=2(1)+3

Now you have x=2+3, which is 5.

x=5 and y=1.

To make sure this is correct, plug both the numbers into an equation, let's use the first one now.

2(5)-3(1)=7

7=7

In the end, the euqtaion equals 7, which means the answer is correct.

User Endrias
by
4.8k points
5 votes

Answer:

x=5

y=1

Explanation:

First, put x=2y+3 inside 2x, which is the top equation. This will come out as 2(2y+3)-3y=7.

If you distribute, it would become 4y-6-3y=7. Then you have to combine like terms to get y+6=7

Add 6 on both sides to get y=1.

Put the value of y, which is 1 into the top or bottom equation. I would prefer the bottom equation because it is simpler. The equation would come out as

x=2(1)+3

x=2+3

x=5

User Jed Veatch
by
5.9k points